2018
DOI: 10.1038/s41430-018-0204-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an easy questionnaire on the assessment of salt habit: the MINISAL-SIIA Study Program

Abstract: The main results of the study indicates that a higher score of this short questionnaire is distinctive of habitual high salt consumption in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…The second step was a literature search on questionnaire development and food literacy [13,14,27,28]. This brought to the first version of the questionnaire, phrased in a comprehensible language, avoiding the use of technical-scientific terms, and tested on a pilot sample of 300 adolescents and adults with different educational and occupational levels (exploratory factor analysis).…”
Section: Development Of a Salt Literacy Questionnairementioning
confidence: 99%
“…The second step was a literature search on questionnaire development and food literacy [13,14,27,28]. This brought to the first version of the questionnaire, phrased in a comprehensible language, avoiding the use of technical-scientific terms, and tested on a pilot sample of 300 adolescents and adults with different educational and occupational levels (exploratory factor analysis).…”
Section: Development Of a Salt Literacy Questionnairementioning
confidence: 99%
“…Furthermore, similar to what was reported previously (Lee et al 2014) and was hypothesised in this study, self-reported salt eating habit did translate into the actual amount of salt consumed and may potentially be used as a proxy to determine salt consumption if further developed into a questionnaire. For example, D'Elia, Manfredi, Strazzullo, & Galletti (2019) developed a short questionnaire on the assessment of salt habit in hypertensive patients that reflects their salt intake. Based on the results of the present study, a similar approach may be employed in a younger, healthy population.…”
Section: The Associations Between Salt Taste Preference Self-reported Salt Habit and Salt Intakementioning
confidence: 99%
“…Selfreported dietary data are often inaccurate as salt intake is both obvious (discretionary salt added to foods at the table or during cooking), as well as not-obvious, for example, in processed or packaged foods. Although a number of authors, including ourselves, have developed and validated short dietary assessment food frequency questionnaires to provide an estimate of salt intake that tend to correlate reasonably well with urinary biomarkers [18][19][20][21], such instruments tend to underestimate total 24 h urinary excretion.…”
Section: Introductionmentioning
confidence: 99%